2005
DOI: 10.1021/ja054645g
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Characterization of Short Helical Polyalanine Peptides in Water:  Analysis of 13CO Chemical Shift Data

Abstract: Measured at 2 °C in water, NMR chemical shifts of 13 C═O labeled central alanine residues of peptides W-Lys 5 -t L 3 -Ala n -t L 3 -Lys 5 NH 2 , n = 9, 11, 13, 15, 19 and W-Lys 5 -t L 3 -a-Ala n -A-Inp-t L 2 -Lys 5 NH 2 (a = D-Ala; t L = tert-leucine; Inp = 4-carboxypiperidine) are used to assign j L t and c L t , the N-and C-terminal t L capping parameters and length-dependent values for w Ala (n), the alanine helical propensity for Ala n peptides. These parameters allow Lifson-Roig characterization of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…The enthalpies were calculated using the estimates for basis set superposition error (BSSE) taken from chains of five H-bonds (six formamides) frozen in the geometries assumed in each of the three H-bonding chains of the optimized helices in a manner somewhat similar to that described in an earlier report. 20 Both B3LYP and X3LYP predict results that are reasonably close to the several experimental values for polyalanine, [23][24][25] polyglutamic acid, 26 and polylysine, 27 and some previous predictive 28 theoretical values 20 available. While the experimental values refer to aqueous solution, we note that SM5.2 29 estimates of the differences in free energies of solvation for the α-helix and polyproline II structure of polyalanine are quite small.…”
Section: α-Helicessupporting
confidence: 66%
“…The enthalpies were calculated using the estimates for basis set superposition error (BSSE) taken from chains of five H-bonds (six formamides) frozen in the geometries assumed in each of the three H-bonding chains of the optimized helices in a manner somewhat similar to that described in an earlier report. 20 Both B3LYP and X3LYP predict results that are reasonably close to the several experimental values for polyalanine, [23][24][25] polyglutamic acid, 26 and polylysine, 27 and some previous predictive 28 theoretical values 20 available. While the experimental values refer to aqueous solution, we note that SM5.2 29 estimates of the differences in free energies of solvation for the α-helix and polyproline II structure of polyalanine are quite small.…”
Section: α-Helicessupporting
confidence: 66%
“…Perhaps most important is that these new dispersion-corrected functionals systematically overestimate the interaction enthalpies of folding per residue for all alanine α-helices by a factor of ∼4 12 as compared to several experimental studies, 4649 while the methods that we use here remain in reasonable agreement with those experiments. For example, our calculated values of the enthalpy of folding per residue for folding of acetyl(Ala) 17 NHCH 3 into the helix are −0.7, −0.8, and −1.2 kcal/mol using ONIOM/B3LYP, B3LYP, and X3LYP, respectively, compared to experimental values that range from −0.9 to −1.1 kcal/mol, 4749 and experimental estimates for polylysine 50 and polyglutamic acid 51 give similar values (−1.1 and −1.2 kcal/mol, respectively). Also, the structures of the β-sheets (as judged by the Ramachandran dihedral angles) formed by all alanine hexapeptides fall outside the accepted range of experimental databases, 12,52,53 while the structures calculated using the methods used here remain within the acceptable limits of these databases.…”
Section: Discussionsupporting
confidence: 67%
“…In fitting the related Zimm-Bragg model to circular dichroism data from copolypeptides of alanine and ornithine or lysine, Yang et al 72 found that the nucleation parameter was very sensitive to the chosen dependence of circular dichroism (CD) signal on helix length, and could vary between σ = 0.004 ( v ≈ 0.073) to σ = 0.02 ( v ≈ 0.206) depending on this choice. A further nuance to the interpretation of experiments probing the helix- coil transition is the recent finding by Kennedy et al 27 that the fitted w may depend on the length of the peptide (as we find when comparing the w for Ac-(AAQAA) 2 -NH 2 and Ac-(AAQAA) 2 -NH 3 - see Figure 7). These challenges together complicate the comparison of the LR parameters from theory and experiments.…”
Section: Resultsmentioning
confidence: 68%